Perancangan Sistem Pengarsipan Surat Menggunakan Metode Design Thinking : Studi Kasus: Dinas Tenaga Kerja dan Transmigrasi Kabupaten Sumedang (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Digital transformation has become a strategic step for government institutions in improving administrative efficiency and the quality of public services. One crucial aspect of this process is the management of correspondence archives, which in many cases is still conducted manually, making it inefficient and prone to data inaccuracies. Based on observations and interviews, it was found that the archiving process at the Department of Manpower and Transmigration of Sumedang Regency is still performed manually using Excel spreadsheets, with an average of 15–30 letters processed per day or more than 700 archives per year. This study aims to design a digital letter archiving system using the Design Thinking method, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test, with the research focused up to the Prototype stage. The results indicate that the designed digital archiving system successfully accommodates user needs through a simple, structured, and easy-to-use interface. The final design, presented in the form of a Wireframe, includes several main pages: Login, Forgot Password, Dashboard, Incoming and Outgoing Archives, Add Archive Form, and Add Archive Menu. The application of Design Thinking has proven effective in producing a user-centered system design that supports the implementation of digital transformation within governmental administrative environments.